2013
DOI: 10.1007/s00540-013-1639-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative mortality and morbidities in emergency surgeries

Abstract: State of shock, deteriorated consciousness level, chronic obstructive lung disease, ischemic heart disease, hemorrhage requiring blood transfusion, age over 80 years, cardiovascular surgery, surgeries at night, and surgeries of duration more than 2 h cause patients to be strongly susceptible to postoperative mortality or morbidity in emergency surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…In the study cohort, the mean (SD) age at hospital admission was 56.6 (14.2) years. Most patients were male (64%) and [10][11][12][13][14][15][16][17][18][19][20]. Patient characteristics of the study cohort were stratified according to 90-day mortality ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study cohort, the mean (SD) age at hospital admission was 56.6 (14.2) years. Most patients were male (64%) and [10][11][12][13][14][15][16][17][18][19][20]. Patient characteristics of the study cohort were stratified according to 90-day mortality ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…increased morbidity and mortality are not fully understood, but medical comorbidities and physiological derangements are likely to be contributing factors. [10][11][12][13] Although surgical risk calculation tools such as the American College of Surgeons National Surgical Quality Improvement Project Surgical Risk Calculator are used to gain an objective sense of surgical risk stratification, such tools have yet to be comprehensively studied in this patient population and do not include the use of liver disease-specific assessment tools such as the MELD score in the prediction of outcomes among patients with CLD undergoing EGS. 14 We hypothesized that among patients with CLD who underwent EGS and were treated in the ICU, the MELD score would independently be associated with mortality.…”
mentioning
confidence: 99%
“…Not only the time to surgery influences the outcomes, but shorter operative times of emergency surgeries are also associated with less postoperative complications [37]. Matsuyama et al reported that the mortality and morbidity are significantly lower if emergency surgeries in adults were completed within 120 min, and Kaushal-Deep et al reports better outcomes if operative times are less than 100 min for pediatric emergency surgeries [37,38]. In severely physiologically compromised trauma patients, the damage control strategy is indicated if the operative time would be longer than 90 min [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, since most NSTI patients are severely physiologically compromised, short and efficient debridements might be recommended, as a major difference in mortality rate was noted between the published results of patients with an operating time shorter and longer than 90 min. The risk at more postoperative complications associated with longer operative times should be considered when skin-sparing debridement for NSTIs is contemplated [37,40]. Therefore, the clinical condition of the patient should determine the course of actions and surgical strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown an association between EGS and negative out comes, including higher rates of major complications and death. [3][4][5][6][7][8][9] Compared to patients undergoing elective oper ations, those undergoing emergency open gastrointestinal surgery are up to 5 times more likely to die within 30 days of their operation; they also experience minor and major complications 3 times as often as their elective surgery counterparts. 9 The traditional model of care for EGS patients was an "oncall" system.…”
mentioning
confidence: 99%